Semantic Analysis and Interpretation of Meanings in Word Quotations in KIS Candy Packaging - Suputra, Gusti Ketut Alit; Yakub S, Fifi; Idris, Idris; Tahir, Moh; Ali, Ali (LITPAM, 2022)
A word's meaning can be determined if it has been used in a speech or sentence. The meaning of a word becomes important when it can be linked to someone's memory or something else. This study aims to explore and interpret the linguistic meanings contained in the KIS candy packaging. This study uses a type of qualitative research that describes data using a series of sentences. The object of this research is the quotation of words found on KIS candy packaging. Data collection uses the technique of observing and noting. In addition, the research instrument is the researcher himself as the key instrument. After obtaining research data that is appropriate to the research topic, it will be analyzed using the referential equivalent technique included in the introduction to semantics. The results of the analysis that has been carried out on the research data in the form of words contained in the KIS candy packaging, the researcher obtains sixteen words that will be used as material for analysis in this study. From the sixteen words that have been collected, eight words have pictorial meaning, three words have referential meaning, two words have emotive meaning, two words have a central meaning, and one connotative meaning. The results of this study can provide an overview and knowledge about the shifts and transformations in vocabulary in Indonesian according to the context of the times.